O DIREITO À CIDADE DA POPULAÇÃO EM SITUAÇÃO DE RUA: REFLEXÃO SOBRE O FENÔMENO DA APOROFOBIA E DAS POLÍTICAS HIGIENISTAS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
ABSTRACT This article aims to address the alarming situation of the homeless population in Brazil and the need for effective actions to ensure their fundamental rights, as a foundation for the prevalence of the principle of human dignity. The analysis initially focuses on the Allegation of Non-Compliance with Fundamental Precept No. 976 (ADPF 976), as an important tool to address this social issue. Considering the homeless population as a heterogeneous group that shares extreme poverty, weak or broken family ties and the absence of regular conventional housing, the lack of effective public policies capable of keeping these people in situations of violence and contempt is addressed, in a hypothetical-deductive way and through a literature review and selected scientific articles.  as aporophobia, the hygienist ideology that would be rooted, in addition to the hostile architecture. In addition, it seeks to analyze the possible worsening of the situation of the homeless population due to the economic and social crisis, aggravated by the pandemic, which pushed more people to the streets. Thus, the urgency of the problem faced by public policies for housing, health and work will be revealed. Keywords: Homeless population; Fundamental Rights; Public Policies; Hygienist Ideology.